PENGENDALIAN WAKTU PEMBANGUNAN RUMAH TIPE 86 DI SEMARANG PROVINSI JAWA TENGAH DENGAN MENGGUNAKAN CRITICAL PATH METHOD (CPM) - siliansyah, nico; sari, sely novita; hermawan, anggi (ReTII, 2021)
The house is a building that cannot be separated from human life because the house is a primary need for human. In the word of constructions there are several stages in planning a construction, one of which is planning the work time to complete a project. A project management method is needed to create a schedule that functions as a monitoring medium for the project. With project management can help manage project in terms of planning and organizing to achieve project goals. Project management can maximize the potential of workers as much as possible, minimize the risk of project failure and create the right time, cost, and quality planning framework. The project to be studied is controlling the constructions time of the type 86 house in Semarang, Central Java Province. The purpose of this study is to obtain the optimal completion time in the construction of a type 86 house. In this study will use the Critical Path Method (CPM) to identify activities that are included in the critical path. In this study, it begins by determining work items, calculating the duration and labor requirements of each work item, determining the ralationship between jobs, making a block chart or barchart, making an S curve, creating a network palnning, and ending with determining the critical path of the whole job. In this study, several data were used, including: house plans, labor unit price analysis (AHSP), cost budget plan (RAB), and the curve S as a reference. Calculated using the help of Microsoft Excel software. Based on the result of the analysis and calculations that have been carried out, the required completion time for the construction of a type 86 house in the city of Semarang is 93 days. Keyword : Planning, Time, Network, Work, CPM